A century of Protestant Christianity in Japan - Iglehart, Charles Wheeler (C. E. Tuttle Co., 1959)
A century of Protestant Christianity in Japan has been written by Dr. Charles W. Iglehart in the first instance at the request of the Christan literature commission of the National Christian Council of Japan, as part of the centenary campaign of that body, culminating in 1959. A numer of historical statements have been issued in the Japanese language, but it was felt appropriate that there be a factual and comprehensive account in english,...